The role of photovoice and cellphilms to support women farmers’ climate-resilience strategies - Kawerau, Laura; Welk, Lukas; Birkenberg, Athena; Daum, Thomas; Butele, Cosmas Alfred; Birner, Regina (International Food Policy Research Institute, 2023)
Information and communication technologies (ICTs) can support the collection of agricultural data. While most such data collection efforts have focused on phone surveys, ICT can also facilitate the collection of visual data through photovoice or cellphilms. ICT for visual data has not been widely used nor assessed in the context of agriculture. This note summarizes findings from a qualitative field study on the use of ICT tools for the collection of information on climate-smart agriculture (CSA) practices by women and men farmers in the central region of Uganda. The findings suggest that these visual research tools can increase insights on women’s perceptions, needs, and strategies for agricultural development and climate resilience.